Money In Modern Macro Models: A Review of the Arguments - Seitz, Franz; Schmidt, Markus A. (Journal of Reviews on Global Economics, 2014)
This paper provides an overview of the role of money in modern macro models. In particular, we are focussing on New Keynesian and New Monetarist models to investigate their main findings and most significant shortcomings in considering money properly. As a further step, we ask about the role of financial intermediaries in this respect. In dealing with these issues, we distinguish between narrow and broad monetary aggregates. We conclude that for theoretical as well as practical reasons a periodic review of the definition of monetary aggregates is advisable. Despite the criticism brought forward by the recent New Keynesian literature, we argue that keeping an eye on money is important to monetary policy decision-makers in order to safeguard price stability as well as, as a side-benefit, ensure financial market stability. In a nutshell: money still matters.